Diagnosis and treatment of congenital hemophilia with inhibitors. A Latin American perspective (2008)
The Committee of Latin America on the Therapeutics of Inhibitor Groups (CLOTTING) is composed of a number of hemophilia specialists from Latin America. The group aims to encourage the adoption of a good standard of care for Latin American patients with hemophilia. The occurrence of inhibitors in patients with hemophilia poses clinical challenges, and it is estimated that between 1000 and 3 000 patients in Latin America are affected by hemophilia with inhibitors. There is an urgent need to establish a regional consensus and clinical guidelines for the diagnosis and treatment of these patients. We present an extensive review based on best current clinical practice and published literature, as seen from a Latin American perspective, taking into account the variable nature of hemophilia care available in the various countries in this Region.